Innowacje w sektorze tekstylno-odzieżowym na rynku europejskim - (:unkn) unknown (Wydawnictwo Politechniki Łódzkiej, 2008)
Celem książki jest zaprezentowanie Czytelnikowi wybranych problemów związanych z poprawą innowacyjności przemysłu tekstylno-odzieżowego w celu poprawy jego zdolności do konkurowania zarówno na rynku krajowym, europejskim jak i na rynku globalnym. Produkcja tekstyliów i odzieży od końca lat dziewięćdziesiątych cechuje się w Europie tendencją spadkową ze względu na wysoką konkurencję krajów o niższych kosztach pracy, głownie Indii i Chin. Jak wykazuje szereg badań empirycznych podejmowanych w wielu krajach najlepszą drogą do poprawy konkurencyjności wyrobów tekstylno-odzieżowych jest poprawa ich innowacyjności zarówno w sferze produkcji i technologii jak i nowoczesności produktów i ich lepszego dostosowania do indywidualizujących się w coraz większym stopniu potrzeb odbiorców. Wiele firm, zwłaszcza odzieżowych, najsilniej narażonych na konkurencję firm azjatyckich o niskich kosztach pracy, chcąc utrzymać się na rynku, wybrało strategię outsourcingu jako swego rodzaju innowacji organizacyjnej. W książce innowacje produktowe zostały zaprezentowane na przykładzie takich rynków wyrobów tekstylno-odzieżowych, jak rynek tekstyliów dekoracyjnych, technicznych i medycznych oraz rynek odzieży ochronnej i sportowej. Książka jest adresowana do pracowników i studentów Uniwersytetów i Uczelni Technicznych, jak również do środowiska biznesu działającego na rynku tekstylno-odzieżowym w kraju i za granicą.

The fashion and design industries in the EU make up just 8% of manufacturing value-added, but have experienced low or negative output growth and relatively low R&D spending over recent years. Successful structural adjustment is the key challenge for these industries. Improving innovation, IPR protection, and skills are essential to be able to continue to improve the quality and product-diversity of their output. Obtaining better access to currently heavily protected world markets is also a key policy requirement for these industries.' Home textile market, with special reference to decorative textiles belongs to most important sectors in T &C European industries. In the book there are presented also analysis regarded to knitted fabrics, technical fabrics, technical fabrics and clothing. All EU Member States' markets are covered by the detailed analysis in the period 2000-2005 in the context of the liberalization process within the WTO/ Agreement for Clothing and Textiles and the EU enlargement. The key issue within the EU was to establish the renewed Action Programme for Growth and Employment, as the Programme for the renewed Lisbon Strategy on growth and employment:, entitled: Implementing the Community Lisbon Programme: A policy framework to strengthen EU mamdacturing - towards a more integrated approach .f<Jr industrial policy. To do this the EU priorities were declared to be: • Making Europe a more attractive place to invest and work • Putting knowledge and innovation at the heart of European growth • Shaping policies to allow businesses to create more and better jobs. The policy areas particularly important for the plan to enhance the industrial competitiveness are those that are engaged in processes of: • ensuring an open and competitive Single Market, including competition • knowledge, such as research, innovation, and skills • better regulation • ensuring synergies between competitiveness, energy and environmental policies • ensuring full and fair participation in global markets • facilitating social and economic cohesion2. • Fashion and design industries make up just 8% of manufacturing value-added, but have experienced low or negative output growth and relatively low R&D spending over recent years. • Successful structural adjustment is the key challenge for these industries. • Improving innovation, IPR protection, and skills are essential to be able to continue to improve the quality and product-diversity of their output. Obtaining better access to currently heavily protected world markets is also a key policy requirement for these industries. • Home textiles market, with special reference to decorative textiles is one of the most important sectors of T &C industry in Europe, with the big potential of development and the best prospects for the future. • Adaptation to technical, consumer protection (safety) quality and environmental standards is the key challenge for enterprises to compete in the modernized, innovative home textiles sector in both the European and global markets. The aim of this book is to present the position of the home textiles market and the role of EU member States in this sector in the enlarged Europe, taking into consideration the role of New Members of the EU and the most important exporters from outside Europe: China, India and Bangladesh. All these processes are presented in the context of the renewal Lisbon Strategy and New Industrial Policy of the European Union.
Red. nauk. Wydz. : Kowalski, Krzysztof
Red. Serii : Wodziński, Piotr
Keywords: przemysł włókienniczy; innowacje w przemyśle włókienniczym; sektor tekstylno-odzieżowy; odzież ochronna; tekstylia medyczne; textile industry; innovations in the textile industry; textile and clothing sector; protective clothing; medical textiles